E-Training through E-Platform: Opportunities and Challenges - Al-Ansary, Rofaydah Adnan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the major opportunities and challenges of e-training through e-platforms. A questionnaire has been administered as the main tool to collect the data. The study has adopted the descriptive approach and has been carried out during The second semester of the academic year 1441. The population of the study consisted of the affiliates of the Faculty of Education, Taiba University while the sample of the study comprised 150 participants who were selected as a simple random sampling. Many statistical methods have been used such as frequencies, means, and standard deviation.Findings revealed that the major opportunities and challenges were to give opportunities to involve many trainees in different geographic locations. Findings also showed that technical problems were the major challenge such as slow network, poor connection or sometimes being disconnected which impacted the training process. Findings also revealed that there were no statistically significant differences in the sample views towards opportunities and challenges pertaining to e-training through e-platforms that could be ascribed to gender, qualification, or preferred platforms.The study has concluded with many recommendations; one of which is to affirm the effectiveness of e-training through e-platforms as an important and major entrance to enable the human workforce to align with sustainability goals.
Keywords: E-training; distance training; digital training; e-platforms; open learning sources